Important Criteria in Cultivating Artistic Talents in the 21\(^{st}\) Century: Global Perspectives and China’s Strategy - Xiao, Huang (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
The 21st century is an era of multiple changes happening simultaneously, which include globalization, marketization, urbanization, industrialization, and informatization. They are closely intertwined, forming a superimposed process of mutual influence and mutual promotion. In response to the current complex international situation and contemporary environment, artistic talents should shoulder multiple missions and responsibilities. As a Chinese scholar who has engaged in teaching literary and art theory in several countries, I try to combine the experience gained in the teaching process with academic research, I attempt to shape China’s path through world experience and propose that there should be three main goals for the cultivation of artistic talents in the 21st century. This research identifies key lessons that can inform China’s approach by analyzing how artistic talents are being modelled in various countries. First, artistic talents should be able to contain national and global characteristics that balance regional identity but have universal appeal. Furthermore, they should also be able to develop into professionals in various fields with diverse skills. Finally, artistic talents should have a strong social responsibility by fostering dialog with the public and being able to contribute to the cultural horizon.